Reconsidering the Chronology: Carbonized Food Residue, Accelerator Mass Spectrometry Dates, and Compositional Analysis of a Curated Collection from the Upper Great Lakes. Issue 3 (July 2019) - Kooiman, Susan M.; Walder, Heather
Abstract : Recent reexamination of pottery, copper objects, and glass trade beads using modern analytic methods has amended the occupational history of the Cloudman site (20CH6), once interpreted as an early "Contact" period site in Michigan. The original chronology of the site, located on northern Michigan's Drummond Island in Lake Huron, was based on an apparent association of Iroquoian pottery with European-made trade goods relatively dated to circa AD 1630. Current advances in archaeological dating methods have revealed new insights into the poorly understood settlement patterns and social interactions of various Upper Great Lakes groups between AD 1300 and 1700. Accelerator mass spectrometry dating of carbonized food residue collected from late Late Woodland and Ontario Iroquoian pottery vessels suggests some contemporaneous use of both styles and the culmination of occupation by pottery-making groups by AD 1500. Elemental analysis of glass beads indicates that the recovered trade items were likely manufactured post–AD 1650. Likewise, compositional analysis of copper-base metal artifacts clarifies how such objects were made and used over time at the site. The results demonstrate how the application of modern analytic methods to curated collections can lead to significant reinterpretation, ultimately enhancing understandings of regional chronologies, social relationships, and population movements. Abstract : La reexaminación reciente de cerámica, objetos de cobre y cuentas de vidrio de intercambio usando métodos analíticos modernos ha modificado la historia ocupacional del sitio de Cloudman (20CH6), considerado con anterioridad como el sitio más temprano del periodo de "Contacto" en Michigan. Localizado en la isla Drummond, en el Lago Huron, al norte de Michigan, la cronología original del sitio estuvo basada en una aparente asociación de cerámica iroquesa con productos comerciales de fabricación europea fechados relativamente para el ca. 1630 dC. Avances recientes en los métodos de datación arqueológica han revelado nuevos conocimientos sobre los pobremente entendidos patrones de asentamiento y las interacciones sociales de varios grupos de los Grandes Lagos Superiores entre el 1300 y el 1700 dC. El fechamiento AMS de residuos de comida recolectados de las vasijas de cerámica de la faceta tardía del Woodland Tardío e Iroquesa Ontario sugiere un uso contemporáneo de ambos estilos y la culminación de la ocupación por parte de los grupos alfareros en el año 1500 dC. El análisis elemental de las cuentas de vidrio indica que los artículos de intercambio recuperados probablemente se manufacturaron después del año 1650 dC. Asimismo, el análisis composicional de los artefactos de metal de cobre clarifica como tales objetos fueron manufacturados y usados en el sitio a lo largo del tiempo. Los resultados demuestran como la aplicación de métodos analíticos modernos a colecciones curadas puede llevar a una reinterpretación significativa, lo que en última instancia mejora el entendimiento de las cronologías regionales, relaciones sociales y movimientos poblacionales.